(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Puspitasari M, Abun, Rochana A, Widjastuti T. 2022. The potential of young and old Euphorbia hirta leaves extract as antibacterial against Escherichia coli and antihelminthic against Ascaridia galli obtained in Sentul chickens. Biodiversitas 23: 3243-3250. The declining production of indigenous Sentul chickens is due to pathological microbes in the digestive tract. Euphorbia hirta or patikan kebo is a weed exhibiting active compounds that are expected to remove Escherichia coli and Ascaridia galli from the digestive tracts of chicken. This study aimed to investigate the antibacterial activity of E. coli and anthelmintic A. galli from the ethanol extract of E. hirta. The anthelmintic activity was analyzed in a completely randomized design with four doses (2.5, 5.0, 7.5, and 10 mg/mL) and five replicates. Mortality time series data were subjected to analysis of variance followed by the Duncan test. While a probit analysis determined the Lethal Concentration (LC50) and Lethal Time (LT50), experiments on antibacterial activity were performed by the microdilution method. The result showed a powerful anthelmintic activity in ethanol extracted from both young and old leaves. However, LC50 and LT50 were higher in young leaves than the old ones. While antibacterial activity against E. coli was apparent from ethanol extract in old and young leaves. Old leaves have a Minimum Inhibition Concentration (MIC) of 3.125% lower than young leaves (12.5%).